Experiences Of Female University Student Victims Of Abusive Relationships (A Phenomenological Study on Female University Students in Malang City) - Siwandoyo, Eko Budi; Mayshelda, Florencia Bethrez (International Journal of Multidisciplinary Applied and Science Research, 2025)
This research aims to analyze the subjective experiences of female university students who have been victims of abusive relationships in the context of dating in Malang City. The research uses a descriptive qualitative approach with a phenomenological method to explore the meaning and essence of the victims' experiences in-depth. The main theory used is Lenore Walker's Cycle of Violence Theory, which outlines the recurring pattern of violence in three phases: tension building, acute battering incident, and honeymoon phase. Data were obtained through in-depth interviews, observation, and documentation of three female student informants (RAD, SA, and IAH) selected using purposive sampling technique. Data analysis follows the Miles and Huberman model (data reduction, data display, and conclusion drawing) with source triangulation to ensure data validity. The results show that all three victims experienced various complex and overlapping forms of violence, including physical violence (hitting, slapping, kicking), verbal and psychological violence (cursing, humiliation, emotional control), sexual violence (forced intercourse), digital violence (social media surveillance, privacy violations), and financial violence (economic exploitation, forced taking of money). The relationship dynamics followed Walker's cycle of violence, where accumulated tension exploded into explicit violence, followed by a pseudo-reconciliation phase by the perpetrator. This research concludes that abusive relationships among female university students are a multidimensional phenomenon that traps victims in a manipulative cycle. Efforts to increase awareness, education about healthy relationships, and systematic support from campuses and the environment are needed to prevent and address dating violence.